PENGEMBANGAN E-MODUL MENGGUNAKAN APLIKASI CANVA PADA TEMA SELALU BERHEMAT ENERGI SUBTEMA MANFAAT ENERGI - Elgiana Sukma Hermara; Mira Mirawati; Tatang Muhajang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
E-module is an electronic module that was developed by utilizing the availability of 21st century technology as an effort to improve learning outcomes in accordance with predetermined learning objectives. This research aims to determine the feasibility of using e-modules using the Canva application in the learning process of students on the theme of always saving energy, sub-theme energy benefits. This research uses a Research and Development (R&D) approach, with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of research on e-module development using the Canva application on the theme of always saving energy, sub-theme energy benefits were declared